A Correlation Study on Apolipoprotein Ratio and Malondialdehyde in Patients with Type 2 Diabetes Mellitus - Ayaz Khurram Mallick; Marya Ahsan (Journal of Clinical and Diagnostic Research, 2018)
Introduction: Type 2 Diabetes Mellitus (DM) is associated with hyperglycaemia, dyslipidaemia and oxidative stress. Oxidative damage, indicated by elevated levels of Malondialdehyde (MDA), plays a vital role in development of Coronary Artery Disease (CAD) in diabetics. Although, reduction of Low Density Lipoprotein (LDL) is identified as the primary target for therapy in dyslipidaemic patients by National Cholesterol Education Programme (NCEP), the levels of LDL may not be elevated in diabetic patients. Moreover, many studies have shown that apolipoprotein B100 and A1 (Apo B100 and Apo A1), which are the corresponding protein components of LDL and High Density Lipoproteins (HDL) respectively, are more sensitive markers for screening of CAD. Aim: To determine the concentration of Apo A1 and Apo B100 along with serum MDA in patients with type 2 DM and study the correlation between them. Materials and Methods: A case-control study was done on 75, type 2 diabetic patients and 75 healthy controls. Fasting plasma glucose, glycated haemoglobin, fasting lipid profile along with Apo A1, Apo B100 and MDA as a marker for lipid peroxidation were determined, compared and analysed using SPSS version 23.0. Results: Diabetic patients had a significantly higher levels of serum triglyceride, Apo B100 and MDA along with significantly lower levels of HDL and Apo A1. The Apo B100/Apo A1 ratio was also higher in diabetic cases which showed a strong positive correlation with HbA1c (r=0.515) and MDA (r=0.819). The levels of total cholesterol and LDL were comparable in both the groups. Conclusion: Diabetes mellitus is associated with dyslipidaemia and oxidative stress. Poor glycaemic control is associated with an increased oxidative damage which contributes to development of microvascular complication. Hence, Apo A1, Apo B100 and serum MDA may be included as additional parameters in the management of DM as they could help in early diagnosis and prevention of CAD.